Integrating Space-Based Information And Geographical Information System In Microlevel Planning For Sustainable Development Of Hill Areas - Anil Pal; Vijay Bhuguna; Pinki (Innovative Research Thoughts, 2023)
Effective managernent of natural resources, both renewable and non-renewable, is vital for the existence of mankind in general and the developing world in particular. With the growing population and the consequent demand on the natural resources, it is imperative to adopt a comprehensive and integrated view for the managelnent of these resources. Further, there is an urgent need to pron)0te sustainable and environmentally sound development efforts to preserve eco system of hill area. Resource management practices borne out of ignorance, negligence or lop sided priorities established by power groups, coupled with natural calamities and the complex behavioral pattern of the natural systems, compound the problem in hilly terrain. While, both the urban and rural landscapes will suffer, the major brunt will be borne by the population living in the rural areas. Stuart.L.Hart (1997) Observed that the greatest threat to sustainable development is the depletion of world's renewable resources; water, soils, forests and fisheries are all being pushed beyond their limits by the growth of human population and rapid cutting of forest for agriculture development. Insufficient drinking water may prove to be the most vexing problem in the hilly terrain over the next decade, as agricultural, conunercial and residential uses increase. Water tables are being drawn down at an alartning rate, especially in the most heavily populated nations. More than 10% of the world's topsoil has been seriously eroded. The available cropland and rangeland are shrinking. "Me existing crop varieties are no longer responding to increased use of fertiliser. The world's 1 8 major oceanic fisheries have now reached or actually exceeded their sustainabil ity yields. By some estitnates, the human kind now uses more than 40% of the planet's net primary productivity. If, as predicted, the population doubles over the next 40 years, human kind lilay out-compete most of the animal species for food, driving many to extinction. The non renewable resources such as oil, metals and other mineral resources are finite. We must ensure that the non renewable resources are harnessed at a rate, which ensures that their cost is not prohibitive by the time the society has developed alternatives. Also we need to explore new sources.